2008
DOI: 10.1016/j.crohns.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ulcerative colitis: A population-based, case–control study in Spain

Abstract: Ex-smoking and previous family history of inflammatory bowel disease appeared as risk factors for developing ulcerative colitis while current smoking behaved as a protective factor in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The condition is more and more common worldwide, especially in highly developed societies, and its prevalence varies by geographic region, ranging from 4.9 to 505 per 100 000 in Europe, 4.9 to 168.3 per 100 000 in Asia and the Middle East, and 37.5 to 248.6 per 100 000 in North America [ 3 , 4 ]. The fact that the highest incidence and prevalence of UC are in the populations of Europe and North America is considered to be linked to genetic factors, environment, and lifestyle, particularly to a diet high in fat and sugar, alcohol, medication use, stress, and high socioeconomic status [ 1 , 3 , 5 12 ]. The goal of therapy in UC is to induce and maintain remission, improve quality of life, and prevent colectomy [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The condition is more and more common worldwide, especially in highly developed societies, and its prevalence varies by geographic region, ranging from 4.9 to 505 per 100 000 in Europe, 4.9 to 168.3 per 100 000 in Asia and the Middle East, and 37.5 to 248.6 per 100 000 in North America [ 3 , 4 ]. The fact that the highest incidence and prevalence of UC are in the populations of Europe and North America is considered to be linked to genetic factors, environment, and lifestyle, particularly to a diet high in fat and sugar, alcohol, medication use, stress, and high socioeconomic status [ 1 , 3 , 5 12 ]. The goal of therapy in UC is to induce and maintain remission, improve quality of life, and prevent colectomy [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports had suggested that smokers, particularly those who smoked before the HS, had a less severe form of HS than those who had never smoked . In addition, current smoking is a protective factor in other inflammatory diseases such as ulcerative colitis . Larger studies are needed to determine better the protective effect of tobacco use in patients with HS.…”
Section: Initial Characteristics Of Patients With Hidradenitis Suppurmentioning
confidence: 99%
“… 3 4 5 6 Furthermore, some recent clinical studies have found no association between OCP and the development of IBD. 2 20 21 22 23 24 25 26 These studies were, however, limited by small female sample sizes 20 23 24 25 26 or inclusion of males in the total analyses, 2 21 25 which may result in underpowering and inability to detect an association. Other studies did not evaluate modern OCP formulations.…”
Section: Introductionmentioning
confidence: 99%